Effects of dietary protein and protein energy ratio on growth performance of lemon fin barb hybrid (Hypsibarbus wetmorei X Puntius gonionotus) larvae - Mi'ad, Ros Anizah (2015)
This study was carried out to determine basic requirement of larval Lemon Fin Barb hybrid. There were three experiments in this study. The first experiment is considered as preliminary experiment. The objective is to measure the mouth gape of the larvae. This was done in order to get the right particle size of formulated diet that will be utilized in experiment protein and protein energy ratio requirement of the larvae. The newly hatched larvae were collected from Aquaculture Extension Research Center, Perlok, Pahang, Malaysia. The feeding trial was done in twenty-one days by feeding the larvae with frozen crushed Artemia due to its small mouth gape size than size of Artemia nauplii which ranged from two hundred to four hundred micron. The mouth of larvae opened at the third day after hatched with 49 micrometer mouth gape at 45 degrees. Size of frozen crushed Artemia was 40.93 ± 4.12 micrometer. This size fit well with the mouth gape size of the larvae since day three after hatched. By referring to results obtained in mouth gape study, in subsequent protein and protein energy ratio studies, formulated diet was sieved with 50 micrometer sieve on third day after hatched, on thirteen day after hatched formulated diet was sieved with 100 micrometer sieve and on seventeen day after hatched onwards formulated diet was sieved with 150 micrometer sieve. A series of two experiments were conducted to study the optimum dietary protein level and protein to energy ratio of Lemon Fin Barb hybrid larvae. In experiment one, five formulated diets (4700 kilocalorie per kilogram) ranging from forty to sixty percents protein in five percents increments were fed for twenty-one days to triplicate groups of Lemon Fin Barb hybrid larvae (initial weight: 1.62 ± 0.03 miligram per fish). Larvae were weaned into formulated diet on day six after hatched. From day three to day five after hatched larvae were fed with frozen crushed Artemia in order to develop gustatory response to the digestive system of the larvae. Sampling was done at four days interval. Data on weight, length and survival were taken during sampling process. Weight gain of fish was proportional to the protein content of the diet up to an incorporation rate of fifty percents. Among formulated diets, diet with fifty percents protein recorded the highest weight gain (39.03 ± 0.71 miligram). The dietary protein level that yielded maximum growth was forty-nine percents based on a broken-line model estimation of weight gain. Due to this result, two dietary protein levels (45 percents and 50 percents) were used along with four energy levels at each protein level (4500, 4700, 4900 and 5100 kilocalorie per kilogram diet) in experiment two. In experiment two, eight diets were formulated consisting of protein level (45 percents and 50 percents) with energy level (4500, 4700, 4900 and 5100 kilocalorie per kilogram diet). The survival of fish fed diets containing 45 percents protein was significantly lower (P<0.05) than that of fish fed diets containing 50 percents protein regardless of energy level. Weight gain of fish was significantly (P<0.05) different at all dietary protein and energy levels. The best growth was observed in larvae fed diet 7 containing 50 percents protein with 4900 kilocalorie per kilogram energy with the highest weight gain (43.80 ± 0.64 miligram), best feed conversion ratio (1.05 ± 0.04) and protein energy ratio of 99.36 miligram per kilocalorie. In conclusion Lemon Fin Barb hybrid larvae started opening mouth on third day after hatched at 49 micrometer mouth gape at 45 degrees. The optimum protein level in diet for this new hybrid is fifty percents while the optimum energy is 4900 kilocalorie per kilogram with protein energy ratio of 99.36 miligram per kilocalorie.